Literature and Medicine: Asperger Syndrome in Mark Haddon’s Novel “The Curious Incident of the Dog in the Night-Time” - Andrijaseviæ, Janko (Armenian Folia Anglistika, 2009)
The main protagonist in the novel “The Curious Incident of the Dog in the Night-Time” by the contemporary British writer Mark Haddon, the 15-year-old Christopher, suffers from a mental disorder (Asperger’s Syndrome) and is not aware of the fact. Haddon depicts the world perception of a person with a mental disorder so masterfully and so professionally that the reader involuntarily looks for similarities between himself and the boy. Though the novel does not mention the name of the disease and lacks medical considerations, it is expressed in the novel more effectively and markedly than in any medical report. The article examines the relationship between medicine and literature which represent the two sides of man’s unity and hence must make use of each other’s achievements to shed light on the mystery of the human existence.